Analisis Yuridis terhadap Tugas dan Fungsi Debt Collector Pasca Putusan MK - I Nyoman Suwardika; I Nyoman Suandika; Ida Bagus Anggapurana Pidada (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This research aims to determine the juridical analysis of the duties and functions of Debt Collectors after the Constitutional Court decision and to determine the impact of the post-Constitutional Court Decision on the duties and functions of Debt Collectors. The method used in this research uses the type of research used is a type of juridical analysis approach. The results of the research show that the implementation of the execution of fiduciary guarantees has undergone a change following the decision of the Constitutional Court, which is the term